The Correlation of Students Self Confidence and Their Involving on PIK-R Extracurricular Activity at The Sixht Junior High School - Yetri Hatta Fani; Ismaniar Ismaniar (Universitas Negeri Padang, 2020)
This research was motivated by the successful achievement of scout extracurricular activities in Junior High This research is conducted because of student's low confidence at SMP Negeri 6 Sijunjung, the writer assumes that it caused by the students less involve on PIK-R extracurricular at the school. The aim of this research to (1) describe the students' self-confident at SMP N 6 Sijunjung (2) describe the students involve on PIK-R extracurricular at SMP N 6 Sijunjung (3) find the correlation of students self-confidence and their involving on PIK-R extracurricular activity at SMP Negeri 6 Sijunjung. This research is the correlation with quantitative research. The population is all of the students who involve in PIK-R extracurricular activity at SMP Negeri 6 Sijunjung, about 42 students, the sample of this research about 34 students (80%) of the population. The sample is determining by using a stratified random sampling technique because the population is not homogenous and having proportional? Level the technique used to collect the data in this research is an inquiry by using questionnaires. This research is descriptive and correlational (product-moment) analysis. The result of this research shows that (1) the students at SMP Negeri 6 Sijunjung have less self-confidence (2) the students at SMP Negeri 6 Sijunjung have less involving on PIK-R extracurricular activity (3) there is a significant correlation between students self-confidence and they are involving on PIK-R extracurricular activity at SMP Negeri 6 Sijunjung.Keywords: Self Confidence, Students Involving